Mediated mechanism of thriving at work between perceived organization support, innovative work behavior and turnover intention - Ghulam Abid; Irum Zahra; Alia Ahmed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Thriving at work is a positive psychological state in which individuals experience a sense of vitality and learning. This study is an attempt to analyze thriving at work with two important outcome variables (innovative work behavior and turnover intention) and also examines how perceived organization support transforms individual's psychological states. Using hierarchical linear modeling on an actual sample of 147 employees from a software house, strong support has been found for all the theory-driven hypothesized statements, including the mediating mechanism of thriving at work. This study is probably the first to analyze the mediating mechanism of thriving at work between perceived organization support and innovative work behavior, and turnover intention. The findings of this study significantly contribute to the better understanding of behavior and particularly to the most developing concept of "thriving at work". The study concludes by starring theoretical and practical implications for workers' thriving and suggesting directions for further empirical investigations. However, there are certain limitations as the participants were taken from a single organization. Hence, future studies are required to achieve generalizability of the phenomenon under study.
Keywords: 330; thriving at work; perceived organization support; innovative work behavior; turnover intention